Effect of Mycorrhiza and Lamtoro Leaf Compost on the Growth of Mung Beans (Vigna radiata) in Saline Soil - Aulia Shafra Nadhilah; Yuni Sri Rahayu (LenteraBio : Berkala Ilmiah Biologi, 2026)
Saline soil is one of the alternatives in marginal lands for mung bean cultivation. However, high NaCl and other limiting factors need to be overcome. This study aims to describe the effect of mycorrhiza application and the addition of lamtoro leaf compost on mung bean growth in saline soil. This study used a Randomized Group Design with two treatment factors. The first factor was the concentration of mycorrhiza (0 g, 40 g, and 60 g) and the second factor was the concentration of lamtoro leaf compost (0 g, 50 g, 100 g, and 150 g). Plant growth was examined based on parameter number of leaves, plant height, root length, and biomass of active root nodules, age of first flower, number of flowers, and pod biomass. Data were analyzed using two-way ANOVA followed by Duncan test (p < 0.05). The results showed that the treatment of mycorrhiza 40 g + lamtoro leaf compost 100 g gave the highest results in various parameters recorded. This study also showed that the application of mycorrhiza and lamtoro leaf compost was able to accelerate the generative phase at the age of 45 Days After Planting (DAP).